Comparative proteomic analysis of milk-derived exosomes in human and bovine colostrum and mature milk samples by iTRAQ-coupled LC-MS/MS. (February 2017) - Yang, Mei; Song, Dahe; Cao, Xueyan; Wu, Rina; Liu, Biao; Ye, Wenhui; Wu, Junrui; Yue, Xiqing
Abstract: Exosomes are membranous vesicles found in biological fluids with important functions. However, milk-derived exosome proteins from humans and bovines have not been studied in detail. The advanced iTRAQ proteomic approach was used to analyze milk-derived exosomes in human and bovine colostrum and mature milk samples. A total of 920 milk exosome proteins were identified and quantified. Among these, 575 differentially expressed exosome proteins ( P  < 0.05) were found. Multivariate analysis, gene ontology (GO) annotation and the KEGG pathway were used to interpret the identified proteins. The major biological processes involved were: response to stimulus (22%), localization (16%), establishment of localization (14%), and cellular component organization (14%). Cellular components engaged in intracellular (31%) and intracellular part (31%). The most prevalent molecular function mainly touched upon binding (52%). Milk exosome proteins participated in several KEGG pathways containing ribosome, regulation of actin cytoskeleton, glycolysis/gluconeogenesis, leukocyte transendothelial migration, aminoacyl-tRNA biosynthesis, pentose phosphate pathway, galactose metabolism and fatty acid biosynthesis. These results provide important information on human and bovine milk exosomes, and increase knowledge on the proteomes of these exosomes across different lactation stages, which could provide potential directions for newborn milk powder, biological markers and functional foods. Graphical abstract: The advanced iTRAQ proteomic approach was used to analyze differentially expressed exosome proteins in human and bovine colostrum and mature milk. Highlights: Exosomes are membranous vesicles found in milk with important functions. The iTRAQ-coupled LC-MS/MS is a valuable tool for analysis of milk proteins. Milk-derived exosomes in human and bovine milk are a significant part. Milk-derived exosomes play an important role in the immune system.